1990
DOI: 10.1007/bf01016477
|View full text |Cite
|
Sign up to set email alerts
|

Volatile seed germination inhibitors from plant residues

Abstract: Volatile emissions from residues of the winter cover legumes, Berseem clover (Trifolium alexandrinum L.), hairy vetch [Vicia hirsuta (L.) S.F. Gray], and crimson clover (Trifolium incarnatum L.), inhibited germination and seedling development of onion, carrot, and tomato. Using GC-MS, 31 C2-C10 hydrocarbons, alcohols, aldehydes, ketones, esters, furans, and monoterpenes were identified in these residue emission mixtures. Mixtures of similar compounds were found in the volatiles released by herbicide-treated ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 40 publications
0
40
0
2
Order By: Relevance
“…With regard to allelopathic interactions, plant VOCs are able to generate oxidative stress (Zunino and Zygadlo 2004;Singh et al 2006). In addition, they can affect germination, root and shoot growth (Bradow and Connick 1990;Fischer et al 1994;Kong et al 2002;Singh et al 2002;Barney et al 2005), mitosis and cell size (Romagni et al 2000;Nishida et al 2005), chlorophyll content and fluorescence (Romagni et al 2000;Kong et al 2002;Singh et al 2002), mitochondrial respiration (Abrahim et al 2000(Abrahim et al , 2003Singh et al 2005), DNA synthesis (Nishida et al 2005), and gene expression in exposed plants ). Compared with VOC-mediated plant-plant interaction studies performed aboveground, the amount of published research on the roles played by root VOCs in plant-plant interactions is much lower.…”
Section: Studying Voc-mediated Root-root Interactions: Challenges Andmentioning
confidence: 99%
“…With regard to allelopathic interactions, plant VOCs are able to generate oxidative stress (Zunino and Zygadlo 2004;Singh et al 2006). In addition, they can affect germination, root and shoot growth (Bradow and Connick 1990;Fischer et al 1994;Kong et al 2002;Singh et al 2002;Barney et al 2005), mitosis and cell size (Romagni et al 2000;Nishida et al 2005), chlorophyll content and fluorescence (Romagni et al 2000;Kong et al 2002;Singh et al 2002), mitochondrial respiration (Abrahim et al 2000(Abrahim et al , 2003Singh et al 2005), DNA synthesis (Nishida et al 2005), and gene expression in exposed plants ). Compared with VOC-mediated plant-plant interaction studies performed aboveground, the amount of published research on the roles played by root VOCs in plant-plant interactions is much lower.…”
Section: Studying Voc-mediated Root-root Interactions: Challenges Andmentioning
confidence: 99%
“…), the rus t y grain beetle, Cryptolestes ferrugineus (Stephens), the flat grain beetle, C. pusillus (Schonherr) and the tropical bont tick, Amblyomma variegaturn F. (Pierce et al 1990;Mushobozy et al 1993;Turker et al 1993;Steullet and Guerin 1994;Torto et al 1996;Assad et al 1997;Quiroz and Niemeyer 1998). Nonanal in the volatiles of plants acts as an allelochernic that inhibits seed germination (Bradow and Connick 1990) and probably serves in defence against pathogens and phytophagous insects due to its antifungal properties (Andersen et al 1994) as well as cytotoxic and genotoxic effects (Eck1 et al 1993;Martelli et al 1994). The effect of nonanal in decreasing polymerisation of brain microtubular protein (Miglietta et al 1991), possibly renders it extremely toxic to I. pini which inhabits dead trees where toxic volatiles would be relatively low.…”
Section: Ob) Detection Of Tram-verbenol From the Volatiles Of Poolmentioning
confidence: 99%
“…One possible mechanism that could explain both the residue's inhibitory effect on emergence and early plant growth as well as its differential effect on crop and weed growth is allelopathy. Inhibition of seed germination and early growth of seedlings by compounds derived from crimson clover has been demonstrated under laboratory conditions (Bradow and Connick, 1990;White et al, 1989). Moreover, sensitivity to allelochemicals derived from the clover has been shown to vary among species: White et al (1989), for example, found aqueous extracts of the clover to more negatively affect radicle development of two broad-leaved weed species than that of corn.…”
Section: Other Possible Causes Of the Suppressive Effect Of Crimson Cmentioning
confidence: 99%